Extensive protein hydrolysate formula effectively reduces regurgitation in infants with positive and negative challenge tests for cow’s milk allergy - Vandenplas, Y (Acta Paediatr, 2014)
AIM: Cow’s milk protein allergy (CMPA) is treated using an elimination diet with an extensive protein hydrolysate. We explored whether a thickened or nonthickened version was best for infants with suspected CMPA, which commonly causes regurgitation/vomiting. METHODS: Diagnosis of CMPA was based on a positive challenge test. We compared the efficacy of two casein extensive hydrolysates (eCH), a nonthickened version (NT-eCH) and a thickened version (T-eCH), using a symptom-based score covering regurgitation, crying, stool consistency, eczema, urticarial and respiratory symptoms. RESULTS: A challenge was performed in 52/72 infants with suspected CMPA and was positive in 65.4%. All confirmed CMPA cases tolerated eCH. The symptom-based score decreased significantly in all infants within a month, and the highest reduction was in those with confirmed CMPA. Regurgitation was reduced in all infants (6.4 ± 3.2–2.8 ± 2.9, p < 0.001), but fell more with the T-eCH (−4.2 ± 3.2 regurgitations/day vs. −3.0 ± 4.5, ns), especially in infants with a negative challenge (−3.9 ± 4.0 vs. −1.9 ± 3.4, ns). CONCLUSION: eCH fulfilled the criteria for a hypoallergenic formula, and the NT-eCH and T-eCH formulas both reduced CMPA symptoms. The symptom-based score is useful for evaluating how effective dietary treatments are for CMPA.